Probing dark sectors with long-lived particles at belle II - Filimonova, Anastasiia; Schäfer, Ruth; Westhoff, Susanne (Arxiv, 2019)
We propose a new search for light scalar singlets in rare meson decays. For tiny interactions, the scalar is long-lived at detector scales and decays into displaced pairs of leptons or light mesons. We show that Belle II has a remarkable potential to probe scalars in the GeV range with couplings as small as $10^{-5}$. The predicted sensitivity is higher than at the long-baseline experiments FASER and NA62. We also investigate signatures of invisibly decaying scalars in rare meson decays with missing energy.